add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.
4a - 5b = 74a +5b = 17From the first equation:4a = 7 + 5bsubstitute this value in the second equation:7 + 5b + 5b = 177 + 10b = 1710b = 10b = 1Now,solve for a :4a - 5(1) = 74a = 7 + 54a = 12a = 3
5b + 11 - 2b = 3b + 11
here is how you go about solving it first write down the question 3b+4+5b-1 then change arrangement so that it looks like this 3b+5b+4-1 then solve 8b+3
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
The expression is: (4a+b)/(2a-5b)
3a - 2b
2a+6b
3a - 2b
2a+5b isn't possible the answer is still 2a+5b.
What is the solution of -2a plus 3a plus 5b
5ab-2ab+4a-b+5b = 3ab+4a+4b
5b plus 5-3b-7 is 2b-2.
We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.
4a - 5b = 74a +5b = 17From the first equation:4a = 7 + 5bsubstitute this value in the second equation:7 + 5b + 5b = 177 + 10b = 1710b = 10b = 1Now,solve for a :4a - 5(1) = 74a = 7 + 54a = 12a = 3